2021
DOI: 10.1186/s12967-021-02789-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of EZH2 by chidamide exerts antileukemia activity and increases chemosensitivity through Smo/Gli-1 pathway in acute myeloid leukemia

Abstract: Background Epigenetic dysregulation plays important roles in leukemogenesis and the progression of acute myeloid leukemia (AML). Histone acetyltransferases (HATs) and histone deacetylases (HDACs) reciprocally regulate the acetylation and deacetylation of nuclear histones. Aberrant activation of HDACs results in uncontrolled proliferation and blockade of differentiation, and HDAC inhibition has been investigated as epigenetic therapeutic strategy against AML. Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Wei Guan et al [ 9 ] retrospectively analyzed 17 cases of refractory or relapsed T-lymphocytic lymphoma/leukemia (T-LBL/ALL) and found that chidamide has pleiotropic regulatory immune function and can enhance the sensitivity of tumor cells to chemotherapeutic drugs. Jiang et al [ 10 ] found that chidamide inhibited the proliferation and induced apoptosis of tumor cells and exerted potential anti-leukemia activity. Chidamide can also increase the chemosensitivity of tumor cells by disrupting the Smo/gli-1 pathway and the downstream signaling target p-AKT.…”
Section: Discussionmentioning
confidence: 99%
“…Wei Guan et al [ 9 ] retrospectively analyzed 17 cases of refractory or relapsed T-lymphocytic lymphoma/leukemia (T-LBL/ALL) and found that chidamide has pleiotropic regulatory immune function and can enhance the sensitivity of tumor cells to chemotherapeutic drugs. Jiang et al [ 10 ] found that chidamide inhibited the proliferation and induced apoptosis of tumor cells and exerted potential anti-leukemia activity. Chidamide can also increase the chemosensitivity of tumor cells by disrupting the Smo/gli-1 pathway and the downstream signaling target p-AKT.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular smooth muscle cell growth was assessed with the CCK8 assay kit (Dojindo, Japan), following the kit instructions. 27 Briefly, VSMCs were plated in 96-well plates, and treated with PDGF-BB (30 ng/mL, 24 h), Mdivi-1 (10 μM), PI3K inhibitor (LY294002, 10 μM), and an Akt1/2 kinase inhibitor (IH, 10 μM) for 60 min. After VSMCs were incubated with 10 μL of CCK8 solution for 30 min at 37°C, the absorbance of each well was measured at 450 nm using a spectrophotometer (Thermo Fisher Scientific, USA).…”
Section: Cck8 Assaymentioning
confidence: 99%
“…Chidamide (CHI) is a novel subtype-selective HDACi, that could selectively inhibit the activity of class I (HDAC1, 2, and 3) and class IIb (HDAC10) HDAC with a low concentration, which has been approved to treat peripheral T-cell lymphoma [ 4 ]. It has been reported that CHI could inhibit cell proliferation, induces G0/G1 arrest, increases apoptosis [ 5 , 6 ], and the chemosensitivity [ 7 , 8 ] alone or in combination with other drugs in AML.…”
Section: Introductionmentioning
confidence: 99%